Disain Materi Bacaan untuk Siswa ESP di SMK Kesehatan - Imam Fauzi; Dian Hanifah (Loquen, 2019)
The study attempted to design reading materials for Medical Science at one of Vocational High Schools Medical Science in Serang. To produce satisfactory teaching materials, the researchers did the following steps: doing needs analysis, reviewing the principles of materials design and reading in a foreign language, designing course framework, designing syllabus, designing the reading materials, and implementing the sample lessons. The researchers employed qualitative methods in gathering the data. The instruments used were questionnaire and interview. The questionnaire was addressed to students, alumni, teachers and institution. The interview was collected from the companies or users that have ever recruited the graduated students. The needs analysis was carried out by distributing questionnaires. The results were then analyzed. The result of needs analysis, became the basis for the researchers to design course framework. The course framework was then developed into a syllabus. Finally the syllabus became the basis for designing reading materials. The reading materials for Vocational High School Husada Pratama applied a topical syllabus. Each lesson or unit had different topics, greeting and introduction. Introduction about nurse, health, dioalogue conversation nurse and patient, eat healthy food, profile a nurse, tools, disease, nutrition, the healthy diet pyramid. Each lesson also adopted various reading skills or strategies. They were skimming, scanning, and guessing meaning from context. When the materials had been designed, the researchers implemented six out of ten lessons of the coursebook. The results were satisfactory. Most students mentioned that the coursebook was related to their field of study. The majority of the students also said that the materials were understandable and interesting. They also said that they were satisfied with the reading materials. Keywords: Reading materials, ESP, Reading skill